2017
DOI: 10.1115/1.4036695
|View full text |Cite
|
Sign up to set email alerts
|

Microscale Morphology Effects of Copper–Graphene Oxide Coatings on Pool Boiling Characteristics

Abstract: Enhanced pool boiling heat transfer, with simultaneous increase in critical heat flux (CHF) and heat transfer coefficient (HTC), is desired to improve overall system efficiency and reduce equipment size and cost. This paper focuses on combining graphene oxide (GO) and porous copper particles to generate microstructures based on their ability to enhance HTC, CHF, or both. Three pool boiling performance characteristics based on CHF improvements and wall superheat reductions are identified: Type I-reduction in wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…In mW model, one water molecule is mapped onto one coarse grain bead and water is modeled as an intermediate element between carbon and silicon. The functional form of SW potential is as shown in below equations (2,3,4).…”
Section: Stillinger-weber Based Modelsmentioning
confidence: 99%
“…In mW model, one water molecule is mapped onto one coarse grain bead and water is modeled as an intermediate element between carbon and silicon. The functional form of SW potential is as shown in below equations (2,3,4).…”
Section: Stillinger-weber Based Modelsmentioning
confidence: 99%
“…The thermal conductivity of this section was 391 W/m K (± 9 W/m K). The copper rod was machined to achieve the desired dimensions using a computer based numerically controlled micro-milling process 19 . The surface roughness of the copper surfaces was then reduced to ~ 1.3 μm using a grinding operation.…”
Section: Methods Copper Surfacesmentioning
confidence: 99%
“…Due to unique surface properties and higher thermal conductivity exhibited by graphene (~ 3,000–5,000 W/m K), there has been an ample interest in utilizing graphene-based coatings for heat transfer applications 14 , 15 . Additionally, various surface modification techniques such as chemical vapor deposition 16 , electrodeposition 17 , 18 , sintering 19 , 20 , and electroplating 21 can be adopted to form highly surface-active graphene-based coatings with unique surface features that can impart properties to further improve the heat dissipation rates and overall performance.…”
Section: Introductionmentioning
confidence: 99%
“…They reported 47% and 42% of enhancement in HTC and CHF. In their follow up study, Jaikumar et al [119] presented combined effect of GO with porous copper particles and reported increase in CHF and HTC values. Rishi et al [196] compared GO and composite GO-Cu for boiling heat transfer performance.…”
Section: Carbon Based Nanoparticles Coatingsmentioning
confidence: 99%